Community Engagement (CE) and MyRA Star Rating (MSR): its application and significance / Norhafiza Hassim and Shamsinar Ibrahim - Hashim, Norhafiza; Ibrahim, Shamsinar (Universiti Teknologi MARA, Kedah, 2024)
Community Engagement (CE) and MyRA Star Rating (MSR) constitute integral elements within UiTM's performance indicators, offering guidance to academicians seeking involvement in community-related activities. This strategic initiative serves not only to bridge university intellectuals with communities but also to acknowledge and appreciate their impactful contributions. This article explores the application and significance of CE and MSR as crucial components in fostering meaningful engagement between academia and local communities.